Frailty and Cognitive Impairment in Predicting Mortality Among Oldest-Old People - Hao, Qiukui; Dong, Birong; Yang, Ming; Dong, Biao; Wei, Yuquan (Frontiers in Aging Neuroscience, 2018)
Backgrounds: Frailty and cognitive impairment are critical geriatric syndromes. Both conditions have been identified in old-age adults as increased risk factors for mortality in previous studies. However, the effect of these two jointly syndromes in predicting mortality among people with advanced aged is not well understood. Thus, we used Chinese community cohort to determine an impact of the combined syndromes on the oldest-old people. Methods: Our present study is part of an ongoing project on Longevity and Aging in Dujiangyan, which is a community study on a 90+ year cohort in Sichuan Province in China. Participants were elderly who completed baseline health assessment in 2005 followed by a collection of mortality data in 2009. Frailty and cognitive function were assessed with 34- item Rockwood Frailty Index and the Mini-Mental Status Examination, respectively, and the combined effect(s) of these two parameters on death was examined using the Cox proportional hazard regression model. Results: This study consisted of a total of 705 participants (age = 93.6 ± 3.3 years; 67.4% females), from which 53.8% died during a four-year follow-up period. The prevalence of frailty, cognitive impairment, and the overlap of these two syndromes was 63.7%, 74.2%, and 50.3%, respectively. Our data showed that subjects with combined frailty and cognitive impairment associated with increased risk of death (age, gender, education level, and other potential confounders adjusted); the hazard ratio was 2.13 (95% confidence interval 1.39, 3.24), compared with the control group. However, neither frailty alone nor cognitive impairment alone increased the risk of death in these individuals. Conclusions: The combined frailty and cognitive impairment, other than the independently measured syndromes (frailty or cognitive impairment alone), was a significant risk factor for death among the oldest-old Chinese people.